Role Play As A Solution For Wiraraja Nurse’s Speaking Ability: Action Of Real Live In Nursing Activities - Akhmad Feri Fatoni; Cory Nelia Damayanti (Fakultas Ilmu Kesehatan, 2019)
English as foregn languge attends to be big problem to solve, especially for nurse. Learning focus that positioned English as general course for nurses doesn’t subside effective contribution to increase the fluency of theirs english communicaton. This research is basically aimed to test the nurse’s speaking ability by using Role play. Quantitative analysis (quasy-experiment) is used to measure that there are differences in English communication skills in experimental calss and control class, while the populations are fourth semester of wiraraja university’s nurse students. Pre-test and post-test were used to measure the improving students’s speaking ability. The result of the data analysis show that the experimental post test’s score is higher than control group.. Therefore, it can be conclude that role play improves wiraraja nurses’s speaking ability.